1991
DOI: 10.1300/j076v16n03_01
|View full text |Cite
|
Sign up to set email alerts
|

The Violent and Victimized in the Male Prison

Abstract: A review of the literature on prison violence identi-I Downloaded by [Michigan State University] at 12:41 07 February 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 3 publications
1
56
0
4
Order By: Relevance
“…Several other quantitative studies of the general prison population suggested that physical victimization was less common at older ages and among less naive prisoners (Cooley, 1993;Ekland-Olson et al, 1983;Wooldredge, 1998;Wright, 1991). Yet these studies' relevance to inmate-oninmate victimization among older prisoners was limited because the examined samples came from a small number of prisons and these samples had few (if any) aging inmates, largely because of the low representation of older inmates (50 and above) in the general prison population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several other quantitative studies of the general prison population suggested that physical victimization was less common at older ages and among less naive prisoners (Cooley, 1993;Ekland-Olson et al, 1983;Wooldredge, 1998;Wright, 1991). Yet these studies' relevance to inmate-oninmate victimization among older prisoners was limited because the examined samples came from a small number of prisons and these samples had few (if any) aging inmates, largely because of the low representation of older inmates (50 and above) in the general prison population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers found that the mismatch of inmate types and certain prison environments produced both victimization and offending at the individual level (Wright, 1991a(Wright, , 1991b. For example, Poole and Regoli (1983) showed that inmate characteristics were used to select individuals into types of facilities and suggested that certain facilities fostered the development of inmate codes that mediated the direct effects of inmate characteristics.…”
Section: Integrated Modelmentioning
confidence: 99%
“…At the same time, one may predict that those incoming inmates with juvenile or adult prison experience may be more likely to 'run the rackets' or victimize prisoners in other ways (Irwin, 1980). Recent studies have generally found that violent inmates tend to have more extensive criminal backgrounds and previous bouts of incarceration (Cunningham, Sorensen, & Reidy, 2005;Wright, 1991).…”
Section: Introductionmentioning
confidence: 99%